Dystocia Due To Foetal Ascites In A Buffalo - Rani, R. Uma; Kathiresan, D. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Foetal monstrosity, foetal malpresentation with postural defects of extremities and various foetal abnormalities in foeti and or in dams leads to dystocia (Debasis and Mousumi, 2010 and Dilipkumar and Dhage, 2009). Foetal ascites is a rare type of dropsical condition that can cause dystocia in cows ( Pandit and Singh, 1990, Sunil Chaudhary et al, 1996). Prior to delivery the size of the ascitic foetus may be reduced by single or multiple incisions with an embryotomy knife per vaginum (Arthur et al., 1996). The incidence of foetal ascites in buffaloes is rarely reported. The present article reports a case of dystocia due to foetal ascites in a graded Murrah buffalo and its successful management with a trocar and cannula under field condition